The utility of age-specific cut-offs for visual rating of medial temporal atrophy in classifying Alzheimer's disease, MCI and cognitively normal elderly subjects - Duara, Ranjan; Loewenstein, David A.; Shen, Qian; Barker, Warren; Varon, Daniel; Greig, Maria T.; Curiel, Rosie; Agron, Joscelyn; Potter, Huntington (Frontiers in Aging Neuroscience, 2013)
Background: New research criteria for diagnosing Alzheimer’s disease (AD) in the mild cognitive impairment stage (MCI-AD) incorporate biomarkers to assign a level of certainty to the diagnosis. Structural MRI is widely available but greatly under-utilized for assessing atrophy of structures affected in early AD, such as the hippocampus (HP), because the quantification of HP volumes (HP-v) requires special expertise, and normative values have not been established. Methods: Elderly subjects (n =273) from the Florida ADRC were classified as having no cognitive impairment (cognitively normal, CN), amnestic mild cognitive impairment (aMCI) or AD. Volumes for the hippocampus (HP-v) were measured on structural MRI scans. A validated visual rating system for measuring medial temporal atrophy (VRS-MTA), including hippocampal, entorhinal cortex and perirhinal cortex atrophy was employed. The participants were subdivided into younger (less than or equal to 75 years of age) and older (greater than 75 years of age) subgroups. Results: Volumetric and VRS-MTA measures were equivalent in predicting classification of CN versus aMCI for older (area under the receiver operator curves [aROC]: 0.652 versus 0.723) and younger subjects (aROC: 0.764 versus 0.736). However, for younger AD subjects, aROC values were significantly higher for VRS-MTA measures (0.920) than for volumetric measures (0.847). Relative to HP-v, VRS-MTA score was significantly more correlated to impairment on a range of memory tests and was more associated with progression of aMCI to AD than HP-v. Conclusion: Structural MRI with VRS-MTA assessment can serve as a biomarker for supporting the diagnosis of MCI-AD. Age-adjusted VRS-MTA scores are at least as effective as HP-v for distinguishing aMCI and AD from CN and for predicting progression from aMCI to AD. VRS-MTA is convenient for use in the clinic as well as for clinical trials and can readily be incorporated into a standardized radiological report.